2021
DOI: 10.1002/pon.5835
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of posttraumatic growth and its associated factors among head and neck cancer survivors

Abstract: Objectives Posttraumatic growth (PTG) may improve well‐being among cancer survivors, but a longitudinal study addressing head and neck cancer (HNC) is lacking. This longitudinal study examined PTG trends and determined the associations of physical symptoms and complications, as well as sociodemographic and tumor characteristics on PTG over time among HNC survivors. Methods Participants completed the European Organization of Research and Treatment of Cancer's “Quality of Life Questionnaire—Head and Neck 35” mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…Despite the difficulties of the pandemic scenario, and any negative implications for oncological patients, in our sample we observed an improvement in distress and development of PTG similar to what has been observed in the literature concerning other diseases ( Gori et al, 2021 ; Hamdan et al, 2022 ). As observed in other studies ( Chiesi et al, 2022 ), resilience and PTG are positively correlated, showing how the presence of adaptive and psychological recovery strategies could improve the ability to transform a traumatic event into a resource.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the difficulties of the pandemic scenario, and any negative implications for oncological patients, in our sample we observed an improvement in distress and development of PTG similar to what has been observed in the literature concerning other diseases ( Gori et al, 2021 ; Hamdan et al, 2022 ). As observed in other studies ( Chiesi et al, 2022 ), resilience and PTG are positively correlated, showing how the presence of adaptive and psychological recovery strategies could improve the ability to transform a traumatic event into a resource.…”
Section: Discussionsupporting
confidence: 87%
“…However, it should be noted that not all patients with trauma related to living with cancer could trigger the development of PTG. If the traumatic experience of living with cancer is too intense, it may lead to failure for cognitive reprocessing of the traumatic event to search for meaning, which will hamper the development of PTG [ 17 ]. Hence, it is pivotal to investigate psychosocial intervention which effectively facilitate the development of PTG.…”
Section: Introductionmentioning
confidence: 99%
“…The patient-reported content validity index scores were excellent, and weak bidirectional correlations were found with resilience, depression, and anxiety. Another study found that lower QoL scores at diagnosis and during the first year after diagnosis have a predictive value for patients with head and neck squamous cell carcinoma, independent of other factors, predicting lower overall survival [2,3], and another study examined the correlation between three commonly used instruments for assessing the quality of life of 33 head and neck cancer patients at Mato Grosso Cancer Hospital in Brazil, revealing a positive correlation [31,38,39]. None of the studies did predictive analysis.…”
Section: Discussionmentioning
confidence: 99%